Dengue Fever Virus Envelope Glycoproteins Variability Characterized Bioinformatically - Polanco, Carlos; Uversky, Vladimir N.; Huberman, Alberto; Hernandez-Lemus, Enrique; Rios Castro, Martha; L Oliva, Erika J.; Martz-Garcia, Mireya; Buhse, Thomas; Roldan Gomez, Francisco J.; Vargas-Alarcon, Gilberto; Zazueta, Cecilia; Pimentel-Hernez, Claudia (Current Analytical Chemistry, 2023)
Background: The infection caused by the dengue fever virus is a severe threat to public health on a global scale; nevertheless, there is currently no effective medical treatment or vaccine available to prevent or treat the condition. Objective: To better understand the physicochemical regularities of these proteins, it is necessary to carry out a computational multiparametric study of the amino acid sequences of envelope proteins expressed by the dengue fever virus and obtain a bioinformatics method that can use the subsequences of the training protein group to figure out the preponderant function of a protein, up to its sequence. Methods: Essentially, at the amino acid level, various computational programs were applied to the sequences expressing the dengue virus envelope glycoproteins to determine the PIM 2.0 v profile and the Protein Intrinsic Disorder Predisposition (PIDP) profile of each protein, and then, at the nucleotide level, a set of programs for genomic analysis was applied. Finally, these results were contrasted with statistical tests. Results: The re-creation of structural morphological similarities provided by specific regularities in the PIM 2.0 v profile and PIDP of the proteins from diverse dengue fever virus envelopes made it possible to propose a computer method that employs the PIM 2.0 v profile to identify this group of proteins based on their sequences; based on our findings, this method is a
Keywords: polarity index method